Data-driven approach for reference shaping considering input constraint. Issue 14 (2021) - Suzuki, Motoya; Kaneko, Osamu
Abstract: Data-driven reference shaping method was proposed by Kuwabara et al. (2020). to realize the desired output by shaping the reference signal without any changes of the implemented controller. In the case where the input signal becomes large, such a desired output cannot be realized and an excessive input power leads to crucial failure of the closed loop. To prevent such situations, it is important to take the input into account in the reference shaping design. From these backgrounds, this paper expands the result on data-driven reference shaping by Kuwabara et al. (2020) so as to address the input limitation explicitly. The main key point of the proposed method here is to introduce the saturation element in the reference shaping. The validity of the proposed method is also investigated to show experiment verifications.